Combining food records with in‐depth probing interviews improves quality of dietary intake reporting in a group of South Asian women - Rozanne Kruger; Welma Stonehouse; Pamela Ruth von Hurst; Jane Coad (Elsevier, 2012)
Abstract Objective: To investigate if the addition of an in‐depth interview focused on cultural dietary practices could improve the quality of dietary data from food records among South Asian women in New Zealand. Methods: Cross‐sectional data were collected from 134 South Asian women (≥20 years), living in Auckland. Dietary data were collected using four‐day food records. Nutritional analysis revealed 33.6% under‐reporting of energy intakes. All women were recalled for an in‐depth probing interview focused on culture‐specific foods and dietary practices. Results: The interview revealed extensive use of dairy products and plant oils. The nutrient content of the food record alone and the food record plus interview were compared; median energy intakes were 6,852 kJ vs 7,246 kJ (p<0.001); under‐reporting decreased by 14.2%, and total fat and protein intakes (g/day) increased (p<0.001). Estimates of poly‐ and mono‐unsaturated fatty acids increased significantly (p<0.001) due to greater use of plant oils due to greater use of plant oils replacing saturated fatty acid‐rich fats in food preparation. A significant increase (17%) (p<0.001) in calcium intake reflects the higher dairy intake identified with the interview. Conclusion: The addition of an in‐depth probing interview to a four‐day food record enhanced food intake reporting. Self‐reported dietary assessments in immigrant population groups require quality control for accuracy. Implications: Methods to ensure high‐quality dietary data are essential to assess health outcomes and to inform public health interventions, especially in immigrant populations.